Alterations in nucleotide-binding oligomerization domain-2 expression, pathway activation, and cytokine production in Yao syndrome. (17th February 2018) - McDonald, Christine; Shen, Min; Johnson, Erin E.; Kabi, Amrita; Yao, Qingping
Abstract: Yao syndrome (YAOS) is a systemic autoinflammatory disease (SAID), formerly termed nucleotide-binding oligomerization domain-2 (NOD2)-associated autoinflammatory disease. Due to the recent identification of YAOS, the molecular mechanisms underlying its disease pathogenesis are unclear. With specific NOD2 variants as characteristic genotypic features of YAOS, our study examined NOD2 expression, transcript splicing, signaling pathway activation, and cytokine profiles in peripheral blood mononuclear cells (PBMCs) from 10 YAOS patients and six healthy individuals. All participants were genotyped for NOD2 variants; all YAOS patients were heterozygous for the NOD2 IVS8 +158 variant (IVS8 +158 ) and four patients also carried a concurrent NOD2 R702W variant (IVS8 +158 /R702W haplotype). Resembling other SAIDs, plasma levels of TNFα, IL-1β, IL-6, IFNγ, and S100A12 were unaltered in YAOS patients. Intron-8 splicing of NOD2 transcripts was unaffected by carriage of NOD2 IVS8 +158 . However, NOD2 transcript level and basal p38 mitogen-activated protein kinase (MAPK) activity were significantly elevated in PBMCs from IVS8 +158 YAOS patients. Moreover, these patients' cells had elevated basal IL-6 secretion that was enhanced by muramyl dipeptide (MDP) stimulation. Tocilizumab treatment of a YAOS IVS8 +158 patient resulted in marked clinical improvement. In contrast, MDP-stimulated NF-κB activity was uniquely suppressed in haplotype IVS8 +158 /R702W patients, as was TNFα secretion. Our study demonstrates for the first time that NOD2 expression and pathway activation are aberrant in YAOS, and specific NOD2 genotypes result in distinct NOD2 expression and cytokine profiles. These findings may also help select therapeutic strategies in the future.